The Effect of Online Customer Reviews, Perceived Value, and Perceived Trust on Purchase Intention at the Shopee Marketplace with the Technology Acceptance Model Approach - Fadlil Zulfan Ishomi; Zaenal Abidin (Universitas Negeri Semarang, 2024)
The e-commerce sector in Indonesia faces intense competition among companies with similar business models. To stay competitive, e-commerce platforms like Shopee must understand the factors influencing customer purchase intention. This research explores the determinants of purchase intention in the Shopee marketplace and evaluates their significance. Using a quantitative approach and the Technology Acceptance Model (TAM) framework, this study incorporates additional variables such as online customer reviews, perceived value, and perceived trust. Data were collected through questionnaires distributed via Google Forms using purposive sampling, targeting Shopee users aged 18–40 years with at least one year of shopping experience. A total of 286 respondents participated in the study. The data were analyzed using partial least squares-structural equation modeling (PLS-SEM) with SmartPLS 3. The findings reveal that perceived usefulness, online customer reviews, and behavioral intention directly influence purchase intention. Additionally, factors such as perceived ease of use, perceived value, perceived trust, and attitude toward using have indirect effects on purchase intention. Out of 18 proposed hypotheses, 14 were supported, while 4 were rejected. These results provide critical insights for e-commerce developers and companies like Shopee to craft more effective marketing strategies, particularly those aimed at enhancing customer purchase intention.